Notes and Comments: Adjusting the Nominal Maximum for Tests of Unknown Difficulty - Mason, Geoffrey P. (Canadian Journal of Higher Education, 1978)
The percentage system of grading is still in common use in post-elementary education, and is likely to remain so. It is suggested that some of the difficulties experienced by instructors in attempting to conform to the arbitrary percentage standards of their institutions while setting tests of unknown difficulty may be overcome by using an adjusted maximum based on the performance of the top students in a class.